2018
DOI: 10.1007/jhep03(2018)135
|View full text |Cite
|
Sign up to set email alerts
|

Let there be light from a second light Higgs doublet

Abstract: In this article, we demonstrate that the unexpected peak at around 95 GeV as seen recently by CMS in the di-photon final state can be explained within the type-I twoHiggs-doublet model by means of a moderately-to-strongly fermiophobic CP-even Higgs H. Depending on the Higgs mass spectrum, the production of such a H arises dominantly from vector boson fusion or through a cascade in either pp → tt withIn this context, we also discuss other Higgs anomalies such as the LEP excess in Higgsstrahlung and the observat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 60 publications
2
40
0
Order By: Relevance
“…Other interesting channels are HH + production through an off-shell W boson [17][18][19][20][21] and ZH production through an off-shell A 0 [22]. The couplings of the 125 GeV Higgs boson are constrained to lie close to SM values [23] which means that |s δ | 0.4.…”
Section: Jhep08(2018)025mentioning
confidence: 99%
“…Other interesting channels are HH + production through an off-shell W boson [17][18][19][20][21] and ZH production through an off-shell A 0 [22]. The couplings of the 125 GeV Higgs boson are constrained to lie close to SM values [23] which means that |s δ | 0.4.…”
Section: Jhep08(2018)025mentioning
confidence: 99%
“…At a similar mass, CMS observes a 2.9 σ local excess in the diphoton channel, that could come from gg → h 2 → γγ [56][57][58]. These observations have motivated theorists to propose a number of models [59][60][61][62][63][64][65][66][67][68] A necessary ingredient of the pNGB DM model is an additional scalar h 2 that mixes with the SM Higgs, denoted as h 1 . It is possible to take m h2 = 96 GeV while still being consistent with the cosmic ray excesses.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we examined the recently observed 95 GeV CMS diphoton excess, which has also been explored in various recent studies [40][41][42]. We have shown that for a custodial fiveplet Higgs boson, branching ratios ∼ 10% are needed to explain the excess.…”
Section: Jhep06(2018)137mentioning
confidence: 99%
“…This also opens up the possibility of future LHC diphoton signals from a light exotic Higgs sector. As part of our analysis we briefly explore the recently observed ∼ 3σ diphoton excess by CMS [38] at ∼ 95 GeV, also examined in recent studies [39][40][41][42][43]. Finally, we examine two explicit realizations of these light Higgs sectors in the Georgi-Machacek (GM) and Supersymmetric GM (SGM) models [44] which contain custodial Higgs bosons with small couplings to SM fermions and, in the SGM model, an invisible (neutralino) LSP.…”
Section: Jhep06(2018)137mentioning
confidence: 99%
See 1 more Smart Citation